Stomatal conductance, mesophyll conductance, and transpiration efficiency in relation to leaf anatomy in rice and wheat genotypes under drought. (15th September 2017) - Ouyang, Wenjing; Struik, Paul C; Yin, Xinyou; Yang, Jianchang
Abstract : Genotypes of Oryza sativa, O. glaberrima and Triticum aestivum were investigated for leaf gas-exchange parameters in relation to anatomical characteristics. Species-dependent relationships provide leads for growing rice like dryland cereals. Abstract: Increasing leaf transpiration efficiency (TE) may provide leads for growing rice like dryland cereals such as wheat ( Triticum aestivum ). To explore avenues for improving TE in rice, variations in stomatal conductance ( g s ) and mesophyll conductance ( g m ) and their anatomical determinants were evaluated in two cultivars from each of lowland, aerobic, and upland groups of Oryza sativa, one cultivar of O. glaberrima, and two cultivars of T. aestivum, under three water regimes. The TE of upland rice, O. glaberrima, and wheat was more responsive to the g m / g s ratio than that of lowland and aerobic rice. Overall, the explanatory power of the particular anatomical trait varied among species. Low stomatal density mostly explained the low g s in drought-tolerant rice, whereas rice genotypes with smaller stomata generally responded more strongly to drought. Compared with rice, wheat had a higher g m, which was associated with thicker mesophyll tissue, mesophyll and chloroplasts more exposed to intercellular spaces, and thinner cell walls. Upland rice, O. glaberrima, and wheat cultivars minimized the decrease in g m under drought by maintaining high ratios of chloroplasts to exposed mesophyll cell walls. Rice TE could be improved by increasing the g m / g s ratio via modifying anatomical traits.